2019
DOI: 10.1109/tap.2018.2888727
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Far-Field Radiation From Impedance-Loaded Nanoloops Accelerated by an Exact Analytical Formulation

Abstract: Impedance loading is a common technique traditionally used in the RF to enhance the performance of an antenna, but its application in the optical regime is not as rigorously studied. This is mainly due to a lack of exact analytical expressions that can be used to rapidly predict the radiation properties of loaded nanoantennas. This paper will derive a set of useful analytical expressions for the far-field radiation properties of loop antennas loaded with an arbitrary number of lumped impedances that are valid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…A reasonable question to consider is whether it is possible to redirect this mode towards a different direction. A recent study in [9] has shown that by adding capacitors, the loop may radiate superdirectively in different directions. The full Pareto fronts of the directivity at different angles versus frequency with various loading arrangements are shown in Figure 4.…”
Section: Superdirectivity Phenomenonmentioning
confidence: 99%
See 2 more Smart Citations
“…A reasonable question to consider is whether it is possible to redirect this mode towards a different direction. A recent study in [9] has shown that by adding capacitors, the loop may radiate superdirectively in different directions. The full Pareto fronts of the directivity at different angles versus frequency with various loading arrangements are shown in Figure 4.…”
Section: Superdirectivity Phenomenonmentioning
confidence: 99%
“…Additional applications of optimizations to the study and design of nanoloops can be found in [9,[16][17].…”
Section: Optimization Of Loop Antennasmentioning
confidence: 99%
See 1 more Smart Citation
“…For reliability reasons, this is most often performed using full-wave electromagnetic (EM) simulation models [3]. The literature offers a plethora of optimization techniques, including local [4] (both gradient-based [5][6][7] and derivative free [8]), global [9][10][11][12], multi-criterial [13][14][15], but also specialized methods for uncertainty quantification (statistical analysis [16], robust design [17,18]). As the computational cost of EM-driven design is high, often prohibitive when using conventional methods [19], considerable research efforts have been directed towards acceleration.…”
Section: Introductionmentioning
confidence: 99%